COVID-19: Epidemiology, Pathology, Diagnosis, Treatment, and Impact - Shahriar, Saimon; Rana, Md. S.; Hossain, Md. Sabbir; Karim, Ariful; Mredula, Tasneem N.; Nourin, Nadia; Uddin, Md. Sahab; Amran, Md. Shah (Current Pharmaceutical Design, 2021)
The pandemic, well-known as COVID-19, has been caused by the coronavirus SARS-CoV-2 and it has distinct characteristics from other coronavirus-related epidemics. This pandemic has been ravaging the whole world for more than a year now, and no drugs or vaccines have been found to eliminate this virus from the infected people effectively; only physical measures like social distancing, hand washing and face-mask wearing have been taken to reduce its spread and very recently Veklury (remdesivir) has been permitted by the USFDA to manage the critical patients. This disease can be asymptomatic, but when it is symptomatic, it presents with respiratory problems and cold- or flu-like symptoms, which can be diagnosed with a chest CT and confirmed with RT-PCR tests. In this review, the taxonomy and structure of SARS-CoV-2 and history, transmission, epidemiology, pathology, clinical features and impacts of the COVID-19 have been discussed. A summary of possible drug targets, attempted physical and chemical measures, as well as vaccine candidates, has also been provided. How this coronavirus is different from other coronaviruses, the obstacles in managing this disease and the possibility of a second wave have also been reviewed. This review represents a wide range of information regarding COVID-19 and intends to be used as a comprehensive overview in this regard.
Keywords: second wave